PERAN PANITIA PENGAWAS PEMILU KECAMATAN BESUKI SITUBONDO DALAM MEMINIMALISIR POLITIK UANG PADA PEMILU 2024 - Rahman, Nuril Endi; Mukhlisin, Latutik; Pramudita, Diaz Azis (Jurnal Keadilan Pemilu, 2024)
This study aims to portray the role of the Panwascam Besuki District, which has duties and functions as an electoral supervisory as stipulated in UU No. 7 Tahun 2017 concerning Elections where one of its duties is to prevent the practice of money politics in the sub-district area. The research method uses descriptive qualitative, data collection by observation, in-depth interviews, and documentation. Data analysis was carried out inductively. The result of the study shows that Panwascam Besuki plays a role as an educator for the community by conducting socialization about participatory supervision and the latent dangers of money politics practices to various elements of society. The role of Panwascam as Electoral Supervisory is very central, especially in the sub-district area. The practice of money politics is a latent danger that is difficult to identify and act on. The existing legal instruments are good enough but are still not strong enough to crack down on money politics behavior that has certain patterns and is camouflaged. Panwascam Besuki’s role has been optimal in providing political education for the community, regarding the dangers of money politics through massive outreach activities.